Understanding the local: Themes and Issues in the Experience of Structural Reform in England. (May 2014) - Woods, Philip; Simkins, Tim
The structure of the English school system has been the subject of almost continuous change since the late-1980s. The most recent was commenced by the Conservative–Liberal Democrat Coalition government, which was elected in May 2010. This policy set in train, very quickly, processes through which all schools have been encouraged, and in some cases required, to become independent of local authorities (LAs) and funded directly by central government, the government's vision being to create a complete system of publicly funded 'independent' schools. This article considers some of the implications of these aspirations and the ways in which they have been translated into policy and implemented. It begins by setting the policies of the Coalition government within a context of trends in education policy since 1988, showing how these can be related to three dominant themes: school autonomy, central control and diversity of provision. It then proceeds to consider how these developments can be theorized, suggesting that diversity of governance, legitimacy and agency provide a suitable framework for analysing the emerging English experience. These ideas are then used to examine this experience and draw conclusions about key issues for the future.